Entrepreneurial leadership and innovative behavior: Manager perspective - Mariana, Ana; Hadianto, Bram; Karen, Karen (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
Innovation becomes a keyword for the company to survive in its environmental business. Therefore, the company must establish a suitable leadership style. Based on the previous studies, the entrepreneurial style can be an alternative for managers to lead the company. After applying it, they can innovatively behave. This research investigates and analyzes the association between this leadership and innovative behavior. The population of this study is the managers of a conglomeration firm in Indonesia. Moreover, this study utilizes the required minimum sample of 200 for theory verification, and 216 managers are obtainable as the samples. Hence, this study uses a structural equation model based on covariance to test the hypothesis and concludes that entrepreneurial leadership can effectively enhance the innovative behavior of managers in the workplace.